Coordinated motion control in task space of an autonomous underwater vehicle–manipulator system. (1st August 2015) - Mohan, Santhakumar; Kim, Jinwhan
Abstract: This paper presents a coordinated motion control scheme using a disturbance observer in task space for an autonomous underwater vehicle–manipulator system (UVMS). Since, the UVMS is kinematically redundant in nature, the proposed controller permits self-motion which can be utilized to perform power efficient trajectory tracking and at the same time it also assures that the system is able to track the given desired spatial trajectory with minimal errors (despite the presence of external disturbances, system uncertainties and internal noises). The performance of the proposed coordinated motion control of the UVMS is demonstrated numerically by simulating a few underwater tasks such as payload conveyance. The system's disturbance compensation capabilities are shown and the effects of external disturbances and parameter uncertainties on the station keeping performance are also analyzed. A comparative analysis on power consumption is presented to prove the effectiveness of the proposed scheme. Highlights: This research provides a generalized framework of the coordinated control in task space for a UVMS. The new scheme enables overcoming the difficulty due to parameter uncertainties and disturbances. The unknown disturbances are estimated and compensated through the help of a disturbance observer. The proposed scheme reduces power consumption significantly.